Wave propagation in a pipe conveying two phase flow - Akintoye O. Oyelade; Adegboyega B. Ehinmowo; Oluwasola Oribayo; Yetunde O. Abiodun (Acta Polytechnica)
The study of wave propagation in pipes conveying a two-phase flow is of significant importance in various engineering applications, including the oil and gas, chemical, and nuclear industries. One of the most significant characteristics of a two-phase flow in pipes is the flow velocity whose estimation is achieved by various means. However, such approaches can be very sensitive to the operational and boundary conditions. Therefore, there is a need to develop a reliable approach based on the local flow dynamics and properties of the pipe. In this work, a wave-based approach for estimating the phase and group velocities was developed. The governing equation of the work was derived based on Hamilton, and the Chisolm correlation model was used for the two-phase flow. The dispersion relation of the governing equation is first derived in terms of the traveling wave feature. Then, the exact expressions of the phase velocity and group velocity for the bending waves are obtained. Furthermore, the free vibration frequency characteristics of the two phases was studied. The results indicate that in a single-phase flow, wave dispersion occurs at a wavenumber of 2.1, whereas in a two-phase flow with a vapour quality of 0.2, dispersion occurs at a higher wavenumber of 5.8, demonstrating that increasing vapour quality delays the onset of dispersion. This work contributes to a better understanding of wave propagation in a two-phase flow.